Childhoods in Peace and Conflict
XVII, 245 p. 1 illus.
Keywords: This edited book offers a collection of highly nuanced accounts of children and childhoods in peace and conflict across political time and space. Organized according to three broad themes (ontologies, pedagogies, and contingencies), each chapter explores the complexities of a particular case study, providing new insights into the ways children’s lives figure as terrains of engagement, contestation, ambivalence, resistance, and reproduction of militarisms. The first three chapters challenge dominant ontologies that prefigure childhood in particular ways. These include who counts as a child worthy of protection, questions of voice and participation, and the diminution of agency. The chapters in the second section bring to view everyday pedagogies whereby myriad knowledges, performances, practices, and competencies may function to militarize children’s lives, including in but not limited to advanced (post)industrial societies of the global North. The third and final section includes investigations that foreground questions of responsibility to children. Here, contributors assess, among other things, resilience-building, the exigencies of protection, and the ethics of military recruitment practices targeting children. J. Marshall Beier is Professor in the Department of Political Science at McMaster University, Canada. Jana Tabak is Assistant Professor in the Department of International Relations at the State University of Rio de Janeiro, Brazil. .